2017
DOI: 10.1515/pralin-2017-0026
|View full text |Cite
|
Sign up to set email alerts
|

Providing Morphological Information for SMT Using Neural Networks

Abstract: Treating morphologically complex words (MCWs) as atomic units in translation would not yield a desirable result. Such words are complicated constituents with meaningful subunits. A complex word in a morphologically rich language (MRL) could be associated with a number of words or even a full sentence in a simpler language, which means the surface form of complex words should be accompanied with auxiliary morphological information in order to provide a precise translation and a better alignment. In this paper w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…markup method [15]. Passban et al (2017) proposed two different methods to associate complex words with complete sentences in multiple words or even simpler languages in the S.M.T. model.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…markup method [15]. Passban et al (2017) proposed two different methods to associate complex words with complete sentences in multiple words or even simpler languages in the S.M.T. model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It showed that N.L.M. produced better scores for conditional word probability approximations, so the decoder produced smoother translations [16].…”
Section: Literature Reviewmentioning
confidence: 99%